Growth and development of the lesser mealworm, Alphitobius diaperinus (Panzer) (Coleoptera: Tenebrionidae) on pulse flours (University Journal of Zoology, Rajshahi University, 2007)
Key words: Alphitobius diaperinus; pulse flours; growth; development Univ. j. zool. Rajshahi Univ. Vol.22, 2003. pp. 63-70